Sustainable politics and the crisis of the peripheries Ireland and Greece - Leonard, Liam; Botetzagias, Iosif (Emerald, 2011)
This volume of the Advances in Ecopolitics examines the impact of the economic crisis on peripheral European states such as Ireland and Greece. Following an introductory chapter, it is divided into two geographically-focussed sections, the first on Ireland, the second section on Greece. Specifically the book focuses on governance, sustainable politics and environmental policies, within the context of accelerated growth and the subsequent economic downturn. It examines issues of governance and politics within these peripheral states, in addition to the development of policies within an EU/EC context. The book concludes with a discussion of the future for sustainable politics in the peripheral states of Europe, in the aftermath of the global downturn. Advances in Ecopoliticsis essential reading for all academics, researchers and practioners who are involved in the areas of environmentalism, providing insight and extending understanding of these issues.
Keywords: Nature -- General.; Nature -- Environmental Conservation & Protection.; Business & Economics -- Environmental Economics.; The environment.; Environmentalist thought & ideology.; Environmental policy -- Ireland.; Environmental policy -- Greece.; Sustainability -- Political aspects -- Ireland.; Sustainability -- Political aspects -- Greece.; elektronické knihy; electronic books